Draft genome sequence of a blaNDM-1- and blaOXA-244-carrying multidrug-resistant Escherichia coli D-ST69 clinical isolate from Egypt. (September 2020) - Soliman, Ahmed M.; Ramadan, Hazem; Sadek, Mustafa; Nariya, Hirofumi; Shimamoto, Toshi; Hiott, Lari M.; Frye, Jonathan G.; Jackson, Charlene R.; Shimamoto, Tadashi
Highlights: First draft genome sequence of E. coli strain ST69 producing NDM-1 and OXA-244. Multidrug resistance with MIC of 64 μg/ml for meropenem and 32 μg/ml for doripenem. bla OXA-244 was located on the chromosome (Tn 6237 ). bla NDM-1 was located on an IncI1 type self-conjugative plasmid of >93-kb in size. Spread of OXA-244- E. coli related to the IS 1R -made composite transposon (Tn 6237 ). Abstract: Objectives: This study describes the first draft genome sequence of a multidrug-resistant (MDR) Escherichia coli D-ST69 clinical isolate from Egypt carrying bla NDM-1 and bla OXA-244 . Methods: The strain was isolated in December 2014 from a wound pus swab of a male patient in the city of Kafr El-Sheikh using MacConkey agar containing 2 μg/mL meropenem. The strain was subjected to antimicrobial susceptibility testing, conjugation experiments, and whole-genome sequencing using an Illumina MiSeq platform. Results: The draft genome of the strain (HR14_AS) was 5.08 Mbp in size containing a total of 90 contigs encoding 4677 predicted genes with an average G+C content of 50.7%. Strain HR14_AS belongs to sequence type 69 (ST69), phylogroup D and exhibits an MDR phenotype, with minimum inhibitory concentrations (MICs) of 64 μg/mL and 32 μg/mL for meropenem and doripenem, respectively. Multiple acquired antimicrobial resistance genes conferring resistance to macrolides [ mdf(A) ], fluoroquinolones [ aac( 6' )-Ib -cr], quinolones ( qnrS1 ), trimethoprim ( dfrA14 ), β-lactams ( bla NDM-1, bla OXA-244, bla CTX-M-15, bla OXA-9 and bla TEM-1B ) and aminoglycosides [ aac(3)-IId, aac( 6' )-Ib, aadA1 and aph( 3' )-VI ] were detected. The bla OXA-244 and bla NDM-1 genes were located on the chromosome (Tn 6237 ) and on an IncI1-type self-conjugative plasmid of >93 kb in size, respectively. Conclusions: Here we report the first draft genome sequence of a MDR E. coli D-ST69 isolate carrying bla NDM-1 and bla OXA-244 . Besides clonal expansion of the E. coli ST38 pandemic clone, this study further identified that the spread of OXA-244-producing E. coli could be related to mobilisation of the IS 1R -made composite transposon (Tn 6237 ) carrying bla OXA-244 .